COMPARATIVE STUDY OF OPEN ENDED- GROUP INVESTIGATION LEARNING MODELS AND CONVENTIONAL LEARNING TOWARD CREATIVE THINKING AND SCIENCE PROCESS SKILLS OF X GRADE STUDENTS AT SMA NEGERI 8 SURAKARTA - Maridi, Dyah Hayu N P, Riezky Maya P (P Biologi FKIP UNS Surakarta, 2015)
The aim of this research was to ascertain the difference of:1. Creative thinking between open ended- group investigation learning models and conventional learning of X Grade students at SMA Negeri 8 Surakarta.2. Science process skills between open ended- group investigation learning models and conventional learning of X grade students at SMA Negeri 8 Surakarta. This research was quasi experiment research which used posttest only nonequivalent control group design. This research applied open ended- group investigation learning models in experimental group and conventional (lecture, discussion, experiments) learning models in control group. The population of this research was all of X grade students at SMA Negeri 8 Surakarta in academic year 2012/2013. Sampling techniques used cluster sampling that choosed X.9 as experiment group and X.10 as control group. Data was collected using ability think creatively test, KPS test, observation sheet, and document. The hypotheses analyzed by t-test. Results of hypotheses for creative thingking showed that sig.> 0,05 is 0,206 and tcount< t table is 1,282<2,007 so that Ho is accepted. The test results that the KPS hypotheses for sig.< 0,05 is 0,04 and tcount> t table is 3,009<2,007 so Ho is rejected.Based the result of discussion in this study, the conclusion is: 1. There is no difference of creative thingking between open ended- group investigation learning models and conventional learning at SMA Negeri 8 Surakarta. 2. There is a difference of science process skill between open ended- group investigation learning models and conventional learning at SMA Negeri 8 Surakarta. Keywords: open ended-group investigation learning models, creative thinking, science process skills.